Prognostic Factors for 10-Year Survival in Patients With Hepatocellular Cancer Receiving Liver Transplantation - Lai, Quirino; Viveiros, Andre; Iesari, Samuele; Vitale, Alessandro; Mennini, Gianluca; Onali, Simona; Hoppe-Lotichius, Maria; Colasanti, Marco; Manzia, Tommaso M.; Mocchegiani, Federico; Spoletini, Gabriele; Agnes, Salvatore; et al. (Frontiers in Oncology, 2022)
Background: Long-term survival after liver transplantation (LT) for hepatocellular cancer (HCC) continues to increase along with the modification of inclusion criteria. This study aimed at identifying risk factors for 5- and 10-year overall and HCC-specific death after LT. Methods: 1,854 HCC transplant recipients from ten European centers during the period 1987-2015 were analyzed. The population was divided in three eras, defined by landmark changes in HCC transplantability indications. Multivariable logistic regression analyses were used to evaluate the significance of independent risk factors for survival. Results: Five and ten-year overall survival rates were 68.1% and 54.4%, respectively. Two-hundred forty-two patients (13.1%) had HCC recurrence. Five- and 10-year recurrence rates were 16.2% and 20.3%. HCC-related deaths peaked at two years after LT (51.1% of all HCC-related deaths) and decreased to a high 30.8% in the interval 6-10 years after LT. The risk factors for 10-year overall survival were macrovascular invasion (OR=2.71; P=0.001), poor grading (OR=1.56; P=0.001), HCV status (OR=1.39; P=0.001), diameter of the target lesion (OR=1.09; P=0.001), AFP slope (OR=1.63; P=0.006), and patient age (OR=0.99; P=0.01). The risk factor for 10-year HCC-related death were AFP slope (OR=4.95; P<0.0001), micro- (OR=2.13; P<0.0001) and macrovascular invasion (OR=2.32; P=0.01), poor tumor grading (OR=1.95; P=0.001), total number of neo-adjuvant therapies (OR=1.11; P=0.001), diameter of the target lesion (OR=1.11; P=0.002), and patient age (OR=0.97; P=0.001). When analyzing survival rates in function of LT era, a progressive improvement of the results was observed, with patients transplanted during the period 2007-2015 showing 5- and 10-year death rates of 26.8 and 38.9% (vs. 1987-1996=P<0.0001; vs. 1997-2006=P=0.005). Conclusions: LT generates long-term overall and disease-free survival rates superior to all other oncologic treatments of hepatocellular cancer. The role of liver transplantation in the modern treatment of HCC becomes even more valued when the follow-up period reaches at least ten years. The results of LT continue to improve even when prudently widening the inclusion criteria for transplantation. Despite the incidence of HCC recurrence is highest during the first post-transplant five years, one-third of them occur later, indicating the importance of a life-long follow-up of these patients.